Molecular Surveillance for Lymphoproliferative Disease Virus in Wild Turkeys (Meleagris gallopavo) from the Eastern United States. - Jesse M Thomas; Andrew B Allison; Edward C Holmes; Jamie E Phillips; Elizabeth M Bunting; Michael J Yabsley; Justin D Brown (PLoS ONE, 2015)
Lymphoproliferative disease virus (LPDV) is a poorly understood, oncogenic avian retrovirus of domestic turkeys that has historically been restricted to Europe and Israel. However, a recent study reported LPDV in multiple wild turkey diagnostic cases from throughout the eastern United States of America (USA). To better understand the distribution of LPDV in the eastern USA, we surveyed 1,164 reportedly asymptomatic hunter-harvested wild turkeys from 17 states for the presence of LPDV proviral DNA by PCR. In total, 564/1,164 (47%) turkeys were positive for LPDV. Wild turkeys from each state had a relatively high prevalence of LPDV, although statewide prevalence varied from 26 to 83%. Phylogenetic analysis revealed two major clades of LPDV in the USA, although one was at a low frequency suggesting restricted transmission, as well as significant clustering by state of isolation. To determine the best tissue to target for diagnostic purposes, liver, spleen, and bone marrow were tested from a subset of 15 hunter-harvested wild turkeys and 20 wild turkey diagnostic cases. Overall, bone marrow provided the highest level of detection for both hunter-harvested turkeys and diagnostic cases. The sensitivity of LPDV detection between tissues was not significantly different for diagnostic cases, but was for hunter-harvested birds. These results indicate that LPDV infection is common and widespread in wild turkey populations throughout the eastern USA, even without overt signs of disease.